(untitled) (Archives of Criminology, 1974)
All the young adult prisoners (17-20 years old), discussed in this work were released in Poland in 1961. In that year from 40 prisons were released a total of 6,193 young adults, of whom 1,025 (16.5%) had previous convictions, while 5,168 (83.5%) had received prison sentences for the first time after having reached the age of 17. The basic object of these follow-up studies was to establish the frequency of recidivism among young adult offenders during the 10 years following their release from prison. The overwhelming majority (894) of those who had had previous convictions were subjects of research; a sample of 1,188 prisoners without previous convictions was taken at random. Data forming the basis for dividing young adult offenders into those with prior convictions and those without, did not take into account the period when they were not yet of age, with the exception of time spent in approved schools. This is most significant, since, as was found in juvenile courts of two cities ‒ Warsaw and Łódź – a considerable percentage of those investigated had already faced trial while still juveniles: this percentage amounted among those without previous conviction to 35%; among those with previous convictions ‒ to 56%. Though these data from big city centres cannot be extrapolated in relation to those of the total of the young people studied, who also come from small towns and villages, they are nevertheless significant. When examining the extent of recidivism during the 10-year period after release, it should be borne in mind that among those with previous convictions as well as among those without previous convictions there were some who were socially maladjusted already as children and adolescents (between 10 and 16). The number of previous convictions (including also detainment in approved schools) of young adults were as follows: 79% had been once convicted, 14% ‒ twice, and 4% ‒ three times or more (as concerning the remaining 3% no accurate data were available as to the number of previous convictions). Thus almost one-fifth of those with previous convictions had already before their release in 1961 faced trial at least three times. Data related to the domicile of those investigated before they were sent to prison (released in 1961) are as follows: ‒ 57% of those without previous convictions had urban domiciles, and 43% rural; ‒ 73% of those with previous conviction had urban domiciles and 27% ‒ rural; Among the cases studied, urban residents predominate, notably among those with previous convictions. Subsequent convictions of young adult offenders were checked twice ‒ in 1967 and 1972 on the basis of their criminal records, revealing all the convictions and each prison term. After the end of the l0-year follow-up period, the average age of those investigated with and without previous convictions amounted to 30 years. After the follow-up period ‒ ten years from the time of release from prison in 1961 ‒ frequency of recidivism among former young adult prisoners amounted to: (a) 82% of those with previous convictions were convicted anew; (b) 57% of those without previous convictions were convicted again. As regards this high percentage of recidivism, it should be borne in mind that the cases studied are not representative of the total of young adult offenders but only of those who have been sentenced to imprisonment by the courts and the fact, already mentioned, that a considerable percentage of the young adults studied were socially maladjusted from childhood. Since the ten-year follow-up period was very long, it was divided into two five-year periods: 1961-1966 and 1967-1972. It was found that a very large percentage of young adult offenders were convicted in both the first and the second five years: those without previous convictions ‒ 26%, those with prior convictions ‒ 46%. As regards those convicted in the first five-year period, they account only for 23% of those without and 19% of those with previous convictions. The corrresponding percentages for those convicted in the second fiveyear period only are: 11% and 12%. If we differentiate former young adult prisoners who had no court records and those who did have them in the first five-year period, but committed no offences in the second five-year period, we find that a total of 63% of young adult offenders without and 42% with previous convictions were not convicted again after having reached the age of approximately 22-25 years. Study of the extent of recidivism during the follow-up period showed that among offenders convicted during the two five-year periods there was a marked predominance of recidivists with multiple ‒ at least four ‒ convictions: they accounted for 65% of those without and 61% of those with previous convictions. But among those convicted in only one of the five-year periods there was a predominance of those with only one or two convictions. They accounted for 65% of the relevant category of former young adult prisoners. Research among urban inhabitants without previous convictions revealed markedly more frequent recidivism (75%) than among such living in rural areas (54%). Among the group with previous convictions, 87% of those living in urban areas became recidivists and as many as 77% of those living in rural areas. Thus there exists a substantial group among young adult prisoners living in the rural areas who display a distinct tendency towards recidivism; it was, however, impossible to establish whether those formerly living in rural areas may not during the follow-up period have lived or commuted to work in towns. A remarkable tendency to recidivism was observed not only among young adult offenders who in 1961 had been in prison, after having been convicted of theft of personal property (79% of the subsequent recidivists among those without and 85% of those with previous convictions), but also among those who were convicted of theft of social property (59% and 38%), for offences against the public officials and government offices (60% and 79%), and against life and health (46% and 75%). This seems to confirm the hypothesis that a substantial percentage of those convicted of such offences, are also individuals who suffered from serious social maladjustment at an early age. The results of the present work bear out the findings of various Polish as well as foreign publications to the effect that imprisonment of young adult offenders suffering from social maladjustment is of very little effect. In view of the marked probability that the majority of these young adult offenders revealed even in childhood symptoms of social maladjustment, it is clearly advisable that prophylaxis should concentrate primarily on taking precautions to avoid the appearance of social maladjustment in children and the young.